The unintended consequences of financialisation: Social democracy hamstrung? The pensions dilemma. (November 2017) - Belfrage, Claes
At the end of the Third Way and no sense of its future, social democrats look to Sweden for inspiration. However, Swedish social democracy is in no better condition. Scholarship is starting to grasp the broad outlines of the movement's difficulties. Providing greater depth, this article employs the Social Systems of Innovation and Production approach to analyse Swedish social democracy's current condition by historicising its current policy dilemmas in relation to the public pension system, once the jewel in the crown of the Rehn–Meidner model and the push for economic and industrial democracy, now the constraining legacy of financialisation.